Comparison of particle size methodology and assessment of nanoparticle tracking analysis (NTA) as a tool for live monitoring of crystallisation pathways - Tajber, Lidia; McComiskey, Kate P.M. (My University, 2018)
Sample complexity and polydispersity presents challenges surrounding particle size measurements for nanoparticles (NPs). To ensure the delivery of high quality products to the marketplace it is imperative that this task is performed with the greatest accuracy and certainty. For this reason, particle sizing via more than one technique is critical to the success of the formulation process. Dynamic light scattering (DLS) and nanoparticle tracking analysis (NTA) are techniques that size particles based on their Brownian motion in liquid medium. However, each technique has advantages and disadvantages associated with its application. This study was designed with the intent of comparing these techniques in a critical manner. NPs were formed using three Biopharmaceutics Classification System class II compounds: itraconazole, ketoconazole and posaconazole, using an anti-solvent addition, bottom up method. The impact of polyethylene glycol, polyethylene glycol methyl ether and polyethylene glycol dimethyl ether with a molecular weight 2000 Da, as stabilizers, was assessed using these two particle sizing techniques. Mie light scattering theory was successfully used to explain the relationship between material composition and particle scattering power. A change in material refractive index, associated with an amorphous to crystalline solid state transformation, was predominantly responsible for the observed change in the light scattering power of posaconazole nano-dispersions. The innovative application of NTA for the live tracking of these physical processes was explored for the first time. This novel finding can serve to deepen our understanding of the dynamic crystallisation pathway undertaken by a nanoparticle.
PUBLISHED
Keywords: Nanoparticle tracking analysis; Dynamic light scattering; Itraconazole; Ketoconazole; Posaconazole; Crystallization; Nanoparticle; Nanoscience & Materials; AZOLE ANTIFUNGAL AGENTS; CRYSTALLISATION; DYNAMIC LIGHT-SCATTERING; ITRACONAZOLE; KETOCONAZOLE; NANOPARTICLES; Nanoparticle Tracking Analysis; posaconazole